La valeur des pauvres. Le pari sur l’argent comme médiateur du conflit social contemporain - Gabriel de Santis Feltran (Confins)
In contemporary Brazil, the urban periphery have two recent and dichotomous figurations: the cause of 'urban violence' that calls for more repression and the core of the 'development' which can turn poor people into "middle class". This essay argues that the representation of "urban violence" displaced the center of contemporary "social question" from "the worker" to the "marginal people". The collapse of universalism involved in this shift entails a selective government that categorizes the population in varying degrees of "vulnerability" and levels of "complexity" of state intervention; as a side effect, different regulatory regimes emerge on urban peripheries - e.g., state, "crime" and the religious - that although always in tension, have cognitive cohesion based in monetized markets. The money seems to mediate the relationship between forms of life which, from other perspectives - legal or moral - would be in radical alterity; consumption emerges as a form of common life and mercantile expansion, above all, connects legal and illegal markets, including fostering urban violence that development allegedly would control. The arguments are based on field research and discussions with different research groups, especially in São Paulo and Rio de Janeiro.